2006
DOI: 10.4103/0019-509x.25773
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal Non Hodgkin′s lymphoma chemotherapy alone an effective treatment modality: Experience from a single centre in India

Abstract: BACKGROUND:Gastrointestinal tract (GI) is the most frequently involved extra nodal site in non-Hodgkin's lymphoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our study, 40% of patients, presented with acute/subacute intestinal obstruction and 7% with intestinal perforation requiring surgical resection which was bit more in comparison with the previously published studies which could be due to late presentation. 18 , 20 Abdominal pain was present in 32% and B symptoms in 36% of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, 40% of patients, presented with acute/subacute intestinal obstruction and 7% with intestinal perforation requiring surgical resection which was bit more in comparison with the previously published studies which could be due to late presentation. 18 , 20 Abdominal pain was present in 32% and B symptoms in 36% of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Pediatric PGILs most commonly involve the small and the large gut, in contrast to adults where the stomach is the most common site of involvement. [ 18 19 ] Most of the papers have shown that ileocoecal junction to be the most common site of involvement; followed by the small intestine. [ 7 15 ] Low-grade lymphomas such as MALToma and IPSID have not been reported in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%